Los dioses griegos y sus mitos en Galeno - López Férez, Juan Antonio (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2004)
Galen knew well the Greek literary tradition. He uses Greek gods and their myths with great accuracy. Normally he accepts the usual mythical version, but sometines he attcks some old stories. In general he writes for a select group of learned Roman friends, and therefore mythical references are often light and short in his works. Nevertheless when he is interested in a special mythical explanation he cites Homer, Hesiod, Lyric poets, tragical and comical writers, philosophers and former medical authors.